Visual Semiotic Analysis in the Main Trailer of Barbie (2023) - Fikriyah, Nurul; Hasbi, Muh. (State University of Makassar, 2024)
This study aims to analyze visuals signs in the main trailer of Barbie (2023) by using Roland Barthes' semiotic theory. This analysis will focus on the visual elements in the trailer such as clothing, colors, as well as facial expressions that serve as signs that create meaning and messages for the audience. This study employs descriptive qualitative research design to explore semiotic concepts and to identify patterns of meaning in the observed signs. The object of this study is the main trailer of Barbie (2023) and it is analyzed by employing Roland Barthes' semiotic analysis by paying attention to the denotation and connotation of visual elements appeared in the main trailer and then associated with relevant myths in society. The results of this study reveals the meaning and message contained in the visual elements of the trailer as well as some relevant myths in general, namely relevance based on appearance, perfection and reality, alienation due to lack or irrelevance, and opinions that are always different.Keywords: Barbie, Semiotic, Movie Trailer, Visual Signs